2016
DOI: 10.1111/jpi.12305
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of melatonin on smoke‐induced vascular injury in rats and humans: a randomized controlled trial

Abstract: Smoking is one of the most harmful lifestyles in the world. Very few studies have investigated the effects of melatonin in smoke-induced vascular injury. This study was designed to investigate whether melatonin could protect rats and humans from smoke-induced vascular injury. 32 male rats and a double-blind randomized controlled trial (RCT) containing 63 participants formed the subjects of this study. In rats, 10 mg/kg of melatonin was intraperitoneally injected. Blood samples and abdominal artery were harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 49 publications
0
44
0
Order By: Relevance
“…25 mg melatonin might seem high, but melatonin is considered a safe nontoxic drug, where long‐term treatment showed only mild adverse events comparable to placebo . Nevertheless, the high dosage might have aggravated ED as other studies showed improvement …”
Section: Discussionmentioning
confidence: 99%
“…25 mg melatonin might seem high, but melatonin is considered a safe nontoxic drug, where long‐term treatment showed only mild adverse events comparable to placebo . Nevertheless, the high dosage might have aggravated ED as other studies showed improvement …”
Section: Discussionmentioning
confidence: 99%
“…In patients with NAFLD, treatment with melatonin (2-5 mg/day) for 14 months significantly reduced levels of triglycerides (TG) and low density lipoprotein cholesterol (LDL-C) compared with controls treated with Essentiale [35]. Treatment with melatonin for two weeks significantly reduced free fatty acids (FFA) compared with placebo in cigarette smokers [36]. A study assessing aluminium-induced toxicity in a rat model found that melatonin protected against toxic dyslipidemia by alleviating the aluminum induced increases in total cholesterol (TC), LDL-C, TG, oxidized LDL, and apolipoprotein B100 (apoB100) [37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the increased activity of LGS potentially enhances insulin sensitivity in the liver, which may explain the insulin‐sensitizing effect of melatonin in smoking rats. Additionally, in our previous study, transcription factor nuclear erythroid 2‐related factor 2 (Nrf2) is the key factor in protective properties of melatonin . Through Nrf2 signaling pathway, melatonin is important for the coordinated upregulation of genes in response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The period of daily smoke exposure was 120 minutes, between 9:00‐10:00 and 15:00‐16:00, for 3 months. Melatonin (Sigma‐Aldrich Co. LLC, St. Louis, MO, USA) was dissolved in dimethyl sulphoxide and diluted by normal saline, intraperitoneally injected at a dose of 10 mg/kg/day . After 3 months, the rats were anesthetized by an injection of pentobarbital sodium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation